1988
DOI: 10.1177/00220345880670020101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Buffering Systems in Dental Plaque

Abstract: A semi-micro method was used for investigation of the buffering properties of whole plaque, plaque fluid, and washed plaque bacteria. Artifacts associated with titration of samples containing live bacteria were noted and their effects estimated. All three sample types showed minimal buffering in the region of neutrality, with much stronger buffering in the regions pH 4-5.5 and pH 8-9. For the range pH 4-7, almost 90% of the total buffer capacity of plaque appeared to be accounted for by macromolecules of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 24 publications
4
39
1
1
Order By: Relevance
“…However, no lactate site differences were seen (table 4) perhaps due, by the same mechanism, to an increased lower jaw sucrose exposure (i.e., increased lactate production after the sucrose rinse) compensating for the higher clearance at this site. Surprisingly, the pH at the lower molar sites were lower than the upper molar sites; however, once the lower site pHs were decreased by a higher sucrose exposure, they would remain depressed (table 4) due to the high buffer capacity of whole plaque [Shellis and Dibdin, 1988]. This mechanism, which suggests that lactate loss from plaque is more rapid than pH changes, is supported by the fact that in the current experiment, where clearance was a factor, about 50% less acid (as lactic acid) was found in the 7-min postsucrose samples than the amount of acid required to reach the same pH values in the in vitro acidification experiment , where clearance factors were absent.…”
Section: Discussionmentioning
confidence: 96%
“…However, no lactate site differences were seen (table 4) perhaps due, by the same mechanism, to an increased lower jaw sucrose exposure (i.e., increased lactate production after the sucrose rinse) compensating for the higher clearance at this site. Surprisingly, the pH at the lower molar sites were lower than the upper molar sites; however, once the lower site pHs were decreased by a higher sucrose exposure, they would remain depressed (table 4) due to the high buffer capacity of whole plaque [Shellis and Dibdin, 1988]. This mechanism, which suggests that lactate loss from plaque is more rapid than pH changes, is supported by the fact that in the current experiment, where clearance was a factor, about 50% less acid (as lactic acid) was found in the 7-min postsucrose samples than the amount of acid required to reach the same pH values in the in vitro acidification experiment , where clearance factors were absent.…”
Section: Discussionmentioning
confidence: 96%
“…7 Therefore, most studies investigating saliva buffering capacity have focused on whole stimulated saliva. 4,8 Ericsson 9 reported that there were distinct differences in the stimulated whole saliva buffering capacity of caries-free and caries-active patients when using expensive equipment and complex laboratory techniques for a saliva buffering capacity test. In the case of commercially available caries risk kits, a colour code chart is used as the means to determine saliva buffering ability.…”
Section: Introductionmentioning
confidence: 99%
“…118 Although chemical and mechanical methods of erosion are often considered separately, models such as the differential buffering capacity (DBC) of an acid can predict the mechanical effects of acid demineralization. 117,121 DBC is measured as the gradient of a titration curve at a certain pH value and gives the concentration of acid required to lower the pH by 1. 122 Acids with lower DBC values have been shown to have more severe effects on enamel for short-term exposure than higher DBC values.…”
mentioning
confidence: 99%
“…122 Acids with lower DBC values have been shown to have more severe effects on enamel for short-term exposure than higher DBC values. 117,121 The DBC value of an acid is made up of the pKa and pH values and is therefore considered to be a more reliable marker of erosion properties over long-term exposure, when the pH range is relevant for dietary exposure. 122 Temperature has a significant impact on the kinetics of dissolution.…”
mentioning
confidence: 99%